Studies on the Natural Antifungal Compounds from Yam tubers (Dioscorea Alata. L.). - Aderiye, Babatunde Idowu (Obafemi Awolowo University, 2014)
In order to investigate the biochemical basis of natural resistance of yam peel to fungal infection, a preliminary chromatographic bioassay of four varietal species of Dioscorea; Manihot esculentum Crantz; Solanum aethiopicum Linn.; and Xanthosoma sagittifolium Schott was undertaken. The studies revealed the presence of antifungal compounds from the peel extracts of the root crops. Four prominent antifungal components were obtained from the peels of Dioscorea alata L. out of which the component at Rf 0.38 was fully characterized. The component was identified with the aid of nuclear magnetic resonance, mass spectroscopy and colour reaction as sitosterol. It is a white crystalline solid with a melting point of 138oC.